Preservation of Indonesian in the border area of Aruk, Indonesia and Sarawak, Malaysia - Elva Sulastriana; Herlina Herlina; Try Hariadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Preservation of Indonesian in the border area of Aruk, Indonesia and Sarawak, MalaysiaWest Kalimantan is one of the provinces in Indonesia which has three border areas with Malaysia. Community interactions between countries that have been going on for centuries undeniably lead to language contact which results in people choosing local language so that communication can run effectively. The purpose of this study was to determine the variety of language used around the area, language attitudes, and the preservation of Indonesian in the border area of Aruk, Indonesia and Sarawak, Malaysia. Quantitative and qualitative methods were used in which the data were obtained through observation, questionnaires, and interviews with a total of 150 respondents. The results show that the variety of languages used by students, traders and government circles as the target speakers is Indonesian. Furthermore, the language serves as an instructional language in education settings, the language of communication, a unifying tool as well as the language of government administration, while the other local and regional languages are used in certain limited contexts. Regarding the attitudes, the people on the border of Aruk, Indonesia and Malaysia show a very positive attitude towards Indonesian. The defense strategy is carried out by students, traders, and the local government.Pelestarian bahasa Indonesia di daerah perbatasan Aruk, Indonesia dan Sarawak, MalaysiaKalimantan Barat merupakan salah satu provinsi di Indonesia yang memiliki tiga wilayah perbatasan dengan Malaysia. Interaksi masyarakat antar negara yang telah berlangsung selama berabad-abad tidak dapat dipungkiri menyebabkan terjadinya kontak bahasa yang mengakibatkan masyarakat memilih bahasa daerah agar komunikasi dapat berjalan dengan efektif. Tujuan dari penelitian ini adalah untuk mengetahui ragam bahasa yang digunakan di sekitar kawasan, sikap bahasa, dan pelestarian bahasa Indonesia di kawasan perbatasan Aruk, Indonesia dan Sarawak, Malaysia. Metode yang digunakan adalah metode kuantitatif dan kualitatif di mana data diperoleh melalui observasi, kuesioner, dan wawancara dengan total 150 responden. Hasil penelitian menunjukkan bahwa ragam bahasa yang digunakan oleh kalangan pelajar, pedagang dan pemerintah sebagai penutur sasaran adalah bahasa Indonesia. Selanjutnya, bahasa tersebut berfungsi sebagai bahasa pengantar dalam pendidikan, bahasa komunikasi, alat pemersatu serta bahasa penyelenggaraan pemerintahan, sedangkan bahasa lokal dan regional lainnya digunakan dalam konteks terbatas tertentu. Mengenai sikap, masyarakat di perbatasan Aruk, Indonesia dan Malaysia menunjukkan sikap yang sangat positif terhadap bahasa Indonesia. Strategi pertahanan dilakukan oleh mahasiswa, pedagang, dan pemerintah setempat.